The application of tranexamic acid in joint arthroplasty: A 20-year bibliometric analysis - Zhang, Jun; Zhao, Runhan; Huang, Yanran; Xiong, Chuang; Liang, Hao; Jiwa, Habu; Luo, Xiaoji (Frontiers in Public Health, 2022)
ABSTRACT Background: With the arrival of the era of the aging population, the amount of joint arthroplasty surgery keeps rising, and the articles related to the application of tranexamic acid (TXA) in joint arthroplasty (we called the application of tranexamic acid in joint arthroplasty as TIA in this study) also show a blowout growth. Therefore, we conducted a bibliometric analysis of TIA-related publications to identify the main research trends and hot spots in this field in the last 20 years. (2) Methods: In this study, publications in the field of TIA from January 1, 2002 to December 31, 2021 were searched in the Web of Science Core Collection (WoSCC). A total of 1013 publications were evaluated for specific characteristics with Microsoft Excel software, CiteSpace, VOSviewer, and Online Analysis Platform of Literature Metrology (http://bibliometric.com/). Results: A total of 1013 TIA-related articles were included in this study, and the number of articles in this field has increased yearly over the past 20 years. The USA and China dominated in the field of TIA. The Sichuan University published the most TIA-related articles among all the institutions. Of all the authors, Professor Pei was the most productive author with 64 articles.The lack of international cooperation was a significant problem in this field during the past 20 years. Furthermore, the results of the co-citation analysis and citation bursts analysis revealed that the safety and effectiveness of TIA and the optimal use strategy were the main trends and hotspots for the current and future. Conclusion: This bibliometric study reviewed the evolution trend of TIA research, and identified the countries, institutions, authors and journals that have made significant contributions to this field in the past 20 years, as well as the limitations and deficiencies in this field. In addition, this study revealed that the effectiveness and safety of TIA and the optimal use strategy was the current or future research trend and hotspot in this field.